Manajemen Peningkatan Mutu Pendidikan - Amiruddin Siahaan; Rizki Akmalia; Yuli Amelia; Tiwi Wulandari; Suhada Aulia Fahra hrp; Khadijah Pasaribu (Journal on Education, 2023)
The low quality of education in Indonesia is actually a discussion that has existed for a long time. However, until now the problem of education quality has not been resolved. Quality education is the hope and demand of all education stakeholders. Everyone will certainly prefer to study at institutions that have good quality. On this basis, schools/educational institutions must be able to provide good service and quality so that they are not left behind and are able to compete with other educational institutions